A Simple and a Reliable Method to Quantify Antioxidant Activity In Vivo - María Pilar de Torre; Rita Yolanda Cavero; María Isabel Calvo; José Luis Vizmanos (MDPI AG, 2019)
The characterization of compounds with antioxidant activity is of great interest due to their ability to reduce reactive oxygen species production and, therefore, prevent some age-related diseases. Its antioxidant capacity can be analyzed by different methods both in vitro and in vivo. Caenorhabditis elegans is an in vivo model widely used in ageing research. Until now, available tests analyze functional effects in the worms, so the antioxidant activity of the compound is indirectly monitored. We have developed a simple and a reliable method to quantify internal antioxidant activity in vivo. To validate this method, we analyzed an aqueous green tea extract and two other compounds with a well-known antioxidant activity and without this activity. The results obtained (EC50 green tea = 21.76 ± 1.28 µg/mL; EC50 positive control = 8.50 ± 0.33 µg/mL; negative control EC50 > 500 µg/mL) can help in the design of further in vivo experiments. Thus, our method can be used as a previous screening capable of reducing the gap between in vitro and in vivo assays.